Advanced groundwater remediation active and passive technologies - Simon, F.-G; Meggyes, T.; McDonald, Chris, 1943- (Thomas Telford, 2002)
A number of techniques can be used towards containing and cleaning contaminated groundwater - either by treating or isolating the soil in situ, or by removing it for washing or disposal. Such technologies mean by high energy consumption, and can lead to new environmental problems. Therefore, more efficient and economical techniques are needed to remediate contaminated soil and groundwater.
Based on the workshop "In-situ Reactive Barriers versus Pump-and-Treat" jointly organised by the Division of Waste Treatment and Remedial Engineering, Department of Environmental Compatibility of Materials, Federal Institute for Materials Research and Testing (BAM), Berlin, Germany and the School of Civil Engineering of the University of Leeds on 18-19 Oct. 2001 and held at BAM.
Keywords: Groundwater -- Purification -- Congresses.; Groundwater -- Pollution -- Congresses.; elektronické knihy; electronic books